(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic, since 2019, has contributed to aggravating situations that increase the risk of colonization or infection by multidrug-resistant bacteria, such as the indiscriminate use of antimicrobials. The aim of this study was to investigate the relationship between bacterial resistance and negative clinical outcome. A cross-sectional and retrospective study was carried out, where data were collected from the medical records of patients hospitalized in different hospital units (ICU, ward, isolation and neonatology units), from January to December 2021. Inclusion criteria were patients reported with colonization or infection by multidrug-resistant bacteria during hospitalization and with complete data. There were 128 positive samples, with a mean age of 68.2 years. There was a statistically significant difference in mortality when comparing patients younger than 50 years and the age groups between 70-80 years (p=0.006) and above 80 years (p=0.03). Among the three main pathogens isolated and their high mortality rate, there was no statistically significant difference in terms of the overall mortality rate for Acinetobacter baumannii (p = 0.54), Klebsiella pneumoniae (p = 1) and Pseudomonas aeruginosa (p = 1). = 0.82). A statistically significant result was detected for mortality and use of quinolones (p = 0.047) and a trend towards significance for polymyxin (p = 0.09). It was concluded that there was high mortality in patients colonized or infected by multidrug-resistant bacteria in a hospital setting, mainly over 70 years old. The use of quinolones, aminoglycosides and polymyxin seems to be related to higher mortality.